2011
DOI: 10.1186/1743-422x-8-88
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of porcine circovirus type 2 in piglets from PMWS-affected and -negative farms in Thailand

Abstract: Porcine circovirus type 2 (PCV2) is the major swine pathogen associated with Porcine circovirus associated disease (PCVAD) including post-weaning multisystemic wasting syndrome (PMWS). Currently, there are 4 subtypes of PCV2 (PCV2a, b, c and d) and some epidemiological evidences demonstrated that virulence of PCV2 may relate to its subtypes. Recently, PMWS was observed more frequently in swine farms in Thailand; however, the information regarding to PCV2 subtype involved was limited. Therefore, this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…3). PCV-2b-1A/B has also been identified in Thailand 11 and Uruguay. 20 In China, the PCV2b-1A/B cluster was reported as the major subtype from 2001 to 2009.…”
Section: Full Scientific Reportmentioning
confidence: 99%
“…3). PCV-2b-1A/B has also been identified in Thailand 11 and Uruguay. 20 In China, the PCV2b-1A/B cluster was reported as the major subtype from 2001 to 2009.…”
Section: Full Scientific Reportmentioning
confidence: 99%
“…The PCV2c genotype has only been found in Denmark to date [31]. In recent years, several reports have suggested that PCV2b is the predominant genotype in many countries worldwide, including Brazil [8,11], Canada [14,15], China [17,21,38], Cuba [29], Denmark [12], Germany [30], Japan [32], Korea [1,2,19,20], Slovakia [37], Spain [10], Sweden [33], Switzerland [39], Thailand [18] and the U.S.A. [6,23]. PCV2b might be more pathogenic than PCV2a [16,32].…”
mentioning
confidence: 99%
“…Types a and b seem to have a worldwide distribution, whereas type c has only been found in Denmark (Dupont et al., 2008). Other subtypes described in Asia (d and e) (Wang et al., 2009) (Jantafong et al., 2011) may belong to the previously described subtypes (a, b, c) (Cortey et al., 2011a).…”
Section: Porcine Circovirus Type 2 (Pcv2)mentioning
confidence: 72%